Analisis Konten Karakter Arlecchino dalam Membentuk Praktik Ritual Gacha pada Permainan Genshin Impact - Dzulya Istiqomah; Banung Grahita; Intan Rizky Mutiaz (Jurnal Ilmu Komputer dan Desain Komunikasi Visual, 2025)
This study explores how the character Arlecchino in Genshin Impact influences players to create and disseminate gacha ritual content on digital platforms. The research employs virtual ethnography and content analysis, collecting visual, narrative, and ritual practice data from social media platforms such as X/Twitter, Facebook, TikTok, YouTube, and others. The ritual practice analysis applies Victor Turner’s (1969) performative practice theory to classify ritual stages and forms. The findings reveal that the visual and narrative elements of Arlecchino play a significant role in motivating players to engage in gacha rituals. These rituals foster diverse interpretations and symbolism associated with the materialities used in the practice. This research enriches the understanding of the relationship between character design, digital culture, and player behavior while offering insights for game developers to design elements that enhance player engagement.